Вплив фізичної культури на подолання стресу у студентів вищих навчальних закладів - Гауряк, Олена; Слухенська, Руслана; Єрохова, А.А.; Литвинюк, Н.Я. (Науковий часопис Національного педагогічного університету імені М.П. Драгоманова, 2022)
У статті проаналізовано важлива тема стресу, розглянуті можливі шляхи запобігання стресових станів за допомогою занять фізичними вправами. Світ та Україна зокрема пережили два важких роки пандемії з усіма можливими заборонами, ізоляціями, дистанційним навчанням на усіх рівнях освітнього процесу. Нині Україна перебуває в надзвичайно важкому стані активної війни Росії проти нашої держави. Це породило нові реалії з обмеженнями у навчанні, перебуванні в укриттях, евакуації тощо. Внаслідок усіх цих факторів може знижуватися витривалість, яка дуже необхідна для навчання, навіть якщо воно здійснюється в режимі онлайн. У такій непростій ситуації здатні допомогти різні засоби, найдієвішими з яких є фізичні вправи. Метою дослідження є визначення поняття «стрес» як явища дійсності сучасної людини, що впливає на здоров'я студентів вишів нашої країни; визначення можливих способів щодо зміцнення стресостійкості шляхом фізичних навантажень. Автори рекомендують студентам, за умов дистанційного навчання, перебування вдома, в укритті, щоб запобігти панічним атакам та стресу, дихальну гімнастику, комплекс фізичних вправ на різні групи м’язів, йогу, пілатес тощо.
The article analyzes the important topic of stress, considers possible ways to prevent stressful situations with the help of physical exercises. The world and Ukraine in particular survived two difficult years of the pandemic with all possible bans, isolations, distance learning at all levels of the educational process. Currently, Ukraine is in an extremely difficult state of active Russian war against our country. This gave rise to new realities with limitations in education, staying in shelters, evacuation, etc. As a result of all these factors, stamina, which is very necessary for studying, even if it is done online, can decrease. Various means can help in such a difficult situation, the most effective of which are physical exercises. The purpose of the study is to define the concept of "stress" as a phenomenon of the reality of modern man, which affects the health of students of higher education institutions of our country; determination of possible ways to strengthen stress resistance through physical exertion. Distance learning, fear of war, worries for one's life as new realities of Ukrainian students have further deepened the already rather difficult student life. Physical activity is the best way to relieve psycho-emotional stress, overcome stress, and prevent diseases. Physical exercises help improve mood, gain a sense of confidence, bring the functional state of the body to an optimal level. The authors recommend students, under the conditions of distance learning, stay at home, in shelter, to prevent panic attacks and stress, breathing exercises, a set of physical exercises for different muscle groups, yoga, Pilates, etc. Conclusions were made that physical culture has an extremely favorable effect on the health of students, both physically and psychologically and mentally. However, many students take their health too lightly and neglect to perform complex exercises in physical education classes. Therefore, physical education teachers need to involve students in active sports in order to prevent the negative consequences of stress in their lives
Keywords: стрес, війна, дистанційне навчання, дихальна гімнастика, йога, фізичні вправи.